Best regimens for treating chemo‐naïve incurable squamous non‐small cell lung cancer with a programmed death‐ligand 1 tumor proportion score of 1%–49%: A network meta‐analysis. Issue 1 (17th November 2021) - Fukuda, Nobuhiko; Horita, Nobuyuki; Namkoong, Ho; Kaneko, Ayami; Somekawa, Kohei; Tagami, Yoichi; Watanabe, Keisuke; Hara, Yu; Kobayashi, Nobuaki; Kaneko, Takeshi
Abstract: Background: Non‐small cell lung cancer (NSCLC) is the leading cause of cancer‐related mortality worldwide. It is advisable to select the appropriate treatment based on characteristics of the cancer such as pathology, mutations, and programmed death‐ligand 1 (PD‐L1) levels. In this study, by remarking squamous NSCLC with low PD‐L1 expression without mutations, we investigated the efficacy and safety of regimens that included molecularly targeted drugs such as immune checkpoint inhibitors (ICIs) through a network meta‐analysis. Methods: Databases were searched systematically to identify appropriate articles, in which randomized trials with incurable squamous NSCLC were described. Suitable studies were manually checked by two reviewers. A random model network meta‐analysis was conducted, in which the primary outcome was the overall survival rate. Results: We identified 48 studies, which included 16 391 patients. When a platinum + third‐generation cytotoxic agent regimen (platinum regimen) was a reference, the platinum regimen + pembrolizumab (Pemb) yielded the best results in regard to the overall survival rate when compared with chemotherapy (hazard ratio [HR] = 0.57, 95% confidence interval [CI] = 0.36–0.90, p  = 0.016) followed by the platinum regimen + nivolumab (Niv) + ipilimumab (Ipi) (HR = 0.61, 95% CI = 0.44–0.84, p  = 0.003). However, the efficacy of ICI monotherapy was not statistically different from that of the platinum regimen. Conclusions: The combination therapies, which were the platinum regimen + Pemb and the platinum regimen + Niv + Ipi, rather than ICI monotherapy were effective first‐line agents for treating squamous NSCLC with low PD‐L1 levels. Abstract : Clinicians wonder which treatment is best for patients with squamous lung cancer expressing low programmed death‐ligand 1 and no mutations. This study presents the comparison of regimens including immune checkpoint inhibitors using network meta‐analysis with 48 studies and 16 391 patients. The primary outcome was overall survival. Our main result was that the platinum regimen + pembrolizumab was the best regimen (hazard ratio = 0.57, 95% confidence interval = 0.36–0.90, p  = 0.016).